Governance Quality, Public Health, Education, and Innovation: Study for Novel Implications - Wu, Ning (Frontiers in Public Health, 2022)
Pandemic or worldwide disease is the greatest issue of all time that not only affects human health but also influences the economic, educational, and other activities of the countries, since malaria is among the leading health disease that disrupts the economic system of the country. Therefore, this study aimed to analyze whether educational expenditure and technological innovation influence malarial incidence in emerging economies. This study also examined the role of government effectiveness, government health expenditure, gross domestic growth, human capital, and research and development during the period 2000–2018. Employing panel data approaches, including the slope heterogeneity and cross-sectional dependence, the second-generation unit root test reveals the stationarity of all variables. The study also validated the existence of a long-run relationship between the variables. Based on the asymmetrical distribution properties, this study employed the quantile regression approach. The empirical results asserted that education and technological innovation significantly reduce malarial incidents in the panel economies. Also, government effectiveness, research and development, and human capital adversely affect incidences of malaria. In contrast, gross domestic product is the only factor found that increases malarial incidents during the selected period. Based on the empirical results, this study suggested policy measures that could benefit the governors, policymakers, and scholars.